Beam steering optical switches in AlGaAs via the Burstein-Moss eﬀect - Moss, James L. (2020)
The quest for compact portable devices that exploit the unique nature of quantum superpositions and entanglement, to produce technologies superior to their classical coun terparts, has recently attracted great interest around the world. One such device is a gravimeter based on cold-atom interferometry. Lab−based experiments using this technology have proved capable of measuring local gravitational acceleration with unprecedented resolution. A portable sensor would allow the improved detection of local density variations beneath the Earths surface. Target applications include the detection of sub surface voids, tunnels and pipework. The miniaturisation of such a device is a complex undertaking. The measurement involves the trapping, cooling and measurement of a cloud of 87Rb atoms. A key step in the experimental protocols requires that a 780 nm laser beam be switched oﬀ with a -30 dB extinction ratio in under ∼ 1 ms. If the whole device is to be compact and rugged, the optical switch must also be small and robust. In this thesis we describe a novel optical switching scheme that may be capable of meeting the requirements for an optical switch suitable for use in a compact, portable, gravimeter. A previously reported switching device based on beam steering at near infra−red wavelengths (∼ 900 nm) was redesigned for operation at 780 nm. The beam steering was achieved via a re−conﬁgurable carrier-induced refractive index proﬁle formed inside the ternary alloy, aluminium gallium arsenide, AlGaAs. These switches are fabricated from an AlGaAs p−i−n epitaxial structure. Calculations of the induced refractive index change, ∆n, as a result of carrier injection were undertaken, predicting an eﬀect as strong as ∆n(N = P = 2×1018cm−3) ∼−0.03 for candidate wafer epitaxies at wavelengths of ∼ 780 nm. A microfabrication process was initially developed for a GaAs/AlGaAs-based device, designed for operation as a switch at wavelengths close to 900nm. The optimisation of the process steps included characterisation and reﬁnement of the contact UV photolithography, ohmic contacts, dry etching and device encapsulation. The process ﬂow was then used to fabricate an active beam steering device connected monolithically to passive strip-loaded waveguides, for use at wavelengths between 890 nm and 940 nm. The IV characteristics of the switches that were fabricated in GaAs/AlGaAs have an ideality factor, η ' 2.5±0.1. Electrical dissipation in the device is < 50 mW in the ”ON” state and ∼ 440 mW when switched to the ”OFF” state. The optical extinction ratio for the switch, at a wavelength of 904 nm, was measured to be -13.4 dB. The measured extinction ratio is expected to improve with further development of the measurement system. The connecting passive waveguides into and out of our devices appear to transmit single modes as designed. Rudimentary switching tests reveal time constants on the order of 100 µs. The measured time constants are limited by the measurement technique and set an upper limit for the switching time of the device.